Development of disease-specific growth charts in Turner syndrome and Noonan syndrome - Tsuyoshi Isojima; Susumu Yokoya (Korean Society of Pediatric Endocrinology, 2017)
Many congenital diseases are associated with growth failure, and patients with these diseases have specific growth patterns. As the growth patterns of affected individuals differ from those of normal populations, it is challenging to detect additional conditions that can influence growth using standard growth charts. Disease-specific growth charts are thus very useful tools and can be helpful for understanding the growth pattern and pathogenesis of congenital diseases. In addition, disease-specific growth charts allow doctors to detect deviations from the usual growth patterns for early diagnosis of an additional condition and can be used to evaluate the effects of growth-promoting treatment for patients. When developing these charts, factors that can affect the reliability of the charts should be considered. These factors include the definition of the disease with growth failure, selection bias in the measurements used to develop the charts, secular trends of the subjects, the numbers of subjects of varying ages and ethnicities, and the statistical method used to develop the charts. In this review, we summarize the development of disease-specific growth charts for Japanese individuals with Turner syndrome and Noonan syndrome and evaluate the efforts to collect unbiased measurements of subjects with these diseases. These charts were the only available disease-specific growth charts of Turner syndrome and Noonan syndrome for Asian populations and were developed using a Japanese population. Therefore, when these charts are adopted for Asian populations other than Japanese, different growth patterns should be considered.